Locating and Identifying Third-Party Decision-Makers - Appel, Jacob M (The journal of the American Academy of Psychiatry and the Law, 2022)
The use of third-party decision-makers such as proxies and surrogates for incapacitated patients has become widespread in the United States. More recently, lawmakers and ethicists have grappled with the challenge of rendering decisions for unbefriended individuals without an identified third-party decision-maker. Far less attention has been paid to the question of how to determine whether a patient is, in fact, unbefriended. Jurisdictions vary regarding how much effort must be invested by clinicians in locating an appropriate decision-maker and also regarding how certain must clinicians be of the identity of apparent decision-makers before acceding to their decisions. This article collects in tabular form the relevant state statutory language on this subject. A decision-relative, context-based approach for addressing these questions as they arise in clinical practice is then proposed, with application in several composite cases.